Determination of the stress field in the Kopeh Dagh and Eastern Iran regions - ROSTAM, Ghasem Ghorbani (Contributions to Geophysics and Geodesy, 2022)
The land of Iran is situated in a compression zone with a high seismicity rate due to the convergence of Arabian and Eurasian plates. In this study, the stress field of two provinces of Kopeh Dagh and Eastern Iran, which are located in the east and northeast of Iran, has been studied and compared. These two provinces are different in terms of seismicity patterns so that Kopeh Dagh is much more active than Eastern Iran. To achieve this goal, the iterative joint inversion method for stress and fault orientations developed by Vavryčuk (2014) has been used. The average direction of the maximum principal stress (σ1) and the maximum horizontal stress (SHmax) in the study area are estimated to be N30.1°E and N12.1°E, respectively. These directions are in agreement with the convergence of the Arabian plate and the Eurasian plate. The value of the optimal friction coefficient was determined for both regions and it was found that this coefficient is lower in Kopeh Dagh than in Eastern Iran. This indicates a potential relationship of the fault friction with the activity pattern and seismicity of in the region.